Protein phosphatase 2A (PP2A) regulatory subunit B′γ interacts with cytoplasmic ACONITASE 3 and modulates the abundance of AOX1A and AOX1D in Arabidopsis thaliana. Issue 3 (13th October 2014) - Konert, Grzegorz; Trotta, Andrea; Kouvonen, Petri; Rahikainen, Moona; Durian, Guido; Blokhina, Olga; Fagerstedt, Kurt; Muth, Dorota; Corthals, Garry L.; Kangasjärvi, Saijaliisa
Summary: Organellar reactive oxygen species (ROS) signalling is a key mechanism that promotes the onset of defensive measures in stress‐exposed plants. The underlying molecular mechanisms and feedback regulation loops, however, still remain poorly understood. Our previous work has shown that a specific regulatory B′γ subunit of protein phosphatase 2A (PP2A) is required to control organellar ROS signalling and associated metabolic adjustments in Arabidopsis thaliana . Here, we addressed the mechanisms through which PP2A‐B′γ impacts on organellar metabolic crosstalk and ROS homeostasis in leaves. Genetic, biochemical and pharmacological approaches, together with a combination of data‐dependent acquisition (DDA) and selected reaction monitoring (SRM) MS techniques, were utilized to assess PP2A‐B′γ‐dependent adjustments in Arabidopsis thaliana . We show that PP2A‐B'γ physically interacts with the cytoplasmic form of aconitase, a central metabolic enzyme functionally connected with mitochondrial respiration, oxidative stress responses and regulation of cell death in plants. Furthermore, PP2A‐B'γ impacts ROS homeostasis by controlling the abundance of specific alternative oxidase isoforms, AOX1A and AOX1D, in leaf mitochondria. We conclude that PP2A‐B'γ‐dependent regulatory actions modulate the functional status of metabolic enzymes that essentially contribute to intracellular ROS signalling and metabolic homeostasis in plants.